RNA expression profiling from FACS-isolated cells of the Drosophila intestine - Dutta, Devanjali; Xiang, Jinyi; Edgar, Bruce (Current protocols in stem cell biology, 2013)
This unit describes a protocol for the isolation of Drosophila intestinal cell populations for the purpose of cell type-specific transcriptome profiling. A method to select a cell type of interest labeled with green or yellow fluorescent protein (GFP, YFP) by making use of the GAL4-UAS bipartite system and fluorescent-activated cell sorting (FACS) is presented. Total RNA is isolated from the sorted cells and linear RNA amplification is used to obtain sufficient amounts of high-quality RNA for analysis by microarray, RT-PCR, or RNA sequencing. This method will be useful for quantitative transcriptome comparison across intestinal cell types under normal and various experimental conditions. Curr. Protoc. Stem Cell Biol. 27:2F.2.1-2F.2.12. © 2013 by John Wiley & Sons, Inc.